Stereodivergent 1,5-Conjugate Addition with Iminoesters via Pd/Cu Dual Catalysis - Yang, Zi-Jiang; He, Zhi-Tao (Synthesis, 2024)
The first stereodivergent umpolung 1,5-conjugate addition reaction via synergistic Pd/Cu catalysts is reported. By dictating the absolute configuration of each chiral ligand ligated to corresponding metals, all four stereoisomers of the products are easily achieved. A series of amino acid moieties are introduced to the γ-position of the conjugated esters in high yields with excellent diastereoselectivities and enantioselectivities. The downstream transformations highlight the synthetic value of the method.
Keywords: stereodivergent; 1,5-conjugate addition; palladium; copper; synergistic catalysis